2018
DOI: 10.32955/neuje.v1i1.56
|View full text |Cite
|
Sign up to set email alerts
|

Use of Computers in Special Education: Benefits and Outcomes

Abstract: Use of computers as effective technological tools in special education has become prevalent in the recent years since it enhances teaching concepts and skills and increase permanence and generalization of learned concepts and skills. Identifying the current situation and trends in a specific field provides a comprehensive perspective for researchers and practitioners. This study aims to examine the current situation and trends in the studies on special education and computer through content analysis. Scopus da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…When technology-assisted educational applications were evaluated for their use with intellectually disabled individuals, the findings showed that those students performed more successfully in educational applications using technological tools (Baglama et al, 2018). The studies on using technology in mathematics education show that today's constantly changing and developing technological innovations are successfully used in the education of children with intellectual disabilities (Burton et al, 2013;Pitchford et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…When technology-assisted educational applications were evaluated for their use with intellectually disabled individuals, the findings showed that those students performed more successfully in educational applications using technological tools (Baglama et al, 2018). The studies on using technology in mathematics education show that today's constantly changing and developing technological innovations are successfully used in the education of children with intellectual disabilities (Burton et al, 2013;Pitchford et al, 2018).…”
Section: Introductionmentioning
confidence: 99%